Observation of low‐level wind reversals in the Gulf of Lion area and their impact on the water vapour variability. (19th April 2016) - Di Girolamo, P.; Flamant, C.; Cacciani, M.; Richard, E.; Ducrocq, V.; Summa, D.; Stelitano, D.; Fourrié, N.; Saïd, F.
Abstract : Water vapour measurements from a ground‐based Raman lidar and an airborne differential absorption lidar, complemented by high‐resolution numerical simulations from two mesoscale models (AROME‐WMED and Meso‐NH), are considered to investigate three transition events from Mistral/Tramontane to southerly marine flow taking place in the Montpellier region (southern France) in the time frame September–October 2012, during the Hydrological Cycle in the Mediterranean Experiment Special Observation Period 1. Low‐level wind reversals associated with these transitions are found to have a strong impact on water vapour transport, leading to a large variability of the water vapour vertical and horizontal distributions. Water vapour mixing ratio within the boundary layer is found to vary from typical values in the range 4–8 g kg −1 during the Mistral/Tramontane flows to values in the range 8–15 g kg −1 during the southerly marine flows. The increase/decrease in water vapour mixing ratio within the boundary layer may be abrupt and marked during these transition periods, with values increasing/decreasing by a factor of 2–4 within 1 h. The high spatial and temporal resolutions of the lidar data allow monitoring the time evolution of the water vapour field during these transitions from predominantly northerly Mistral/Tramontane flow to a predominantly southerly flow, permitting identification of the quite sharp separation between these flows, which is also satisfactorily well captured by the mesoscale models. Water vapour measurements from the ground‐based lidar are complemented by particle backscatter measurements from the same system, which reveal the significant variability in the aerosol and cloud fields associated with these transition events.